Total mesorectal excision for cancer: histological and immunohistochemical evidence of nerve removal and risk‐factor analysis. (October 2016) - Moszkowicz, D.; Rougier, G.; Julié, C.; Nyangoh Timoh, K.; Beauchet, A.; Vychnevskaia, K.; Malafosse, R.; Nordlinger, B.; Peschaud, F.
Abstract: Aim: Whether or not nerve‐sparing rectal‐cancer surgery can effectively prevent removal of the pelvic autonomic nerves has not been substantiated microscopically. We aimed to analyse the quality of nerve preservation in female patients by quantifying residual nerve fibres in total mesorectal excision specimens, to analyse pro‐erectile function of the nerve fibres removed and to determine risk factors for pelvic denervation. Method: Serial transverse sections from female patients, 64 ± 18 years of age, were studied after the mesorectal fascia was inked and studied histologically [using anti‐S100 and anti‐neuronal nitric oxide synthase (nNOS) antibodies]. Nerve fibres located within 1 mm of the inked surface were counted and analysed according to type of surgery, tumour location, pT stage, circumferential resection margin and the necessity for a posterior colpectomy. Results: Twelve specimens were analysed. Per specimen, the mean number of nerve‐fibre sections outside the mesorectum was 5.3 ± 3.6 (range: 1–12). The mean number of fibres per specimen was 6.4 ± 4.1 in patients having a low‐rectal tumour and 4.4 ± 2.9 in those with mid or higher rectal tumours ( P = 0.42). The mean number of fibres was higher (9.2) for T4 tumours than for T2/T3 tumours (5.0 ± 3.5), but this difference was not statistically sigmificant ( P = 0.25). Patients having abdominoperineal excision, a posterior colpectomy or a circumferential resection margin of less than 1 mm had significantly more nerve fibres in the specimen (10.6 ± 1.9 vs 4.4 ± 2.8; P = .041). Fibres localized at the anterolateral rectum corresponded to branches of the neurovascular bundle, expressing rich pro‐erectile activity (positive anti‐nNOS immunostaining). Conclusion: The neurovascular bundle is a key risk zone for pelvic denervation during total mesorectal excision. Abdominoperineal excision, posterior colpectomy and an invaded circumferential resection margin are associated with perineal denervation.